82.1k views
1 vote
Simplify the expressions. Show your work.

(X-2) (3x-4)

Please don’t guess

2 Answers

5 votes

Answer:

3x² - 10x + 8

Explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd


(x-2)(3x-4)=(x)(3x)+(x)(-4)+(-2)(3x)+(-2)(-4)


=3x^2-4x-6x+8 combine like terms


=3x^2+(-4x-6x)+8=3x^2-10x+8

User Stusmith
by
5.6k points
1 vote

Answer: 3x^2-10x+8

Explanation:

x*3x+x(-4)+(-2)*3x+(-2)(-4) Foil Method

3x^2-4x-6x+8 Add and subtract like factors

User Raph Levien
by
6.4k points